Psychological Features of Professional Demand and Motivation of Law-Enforcement Officers - Strelnikova, Yu.Yu; Goncharova, N.A. (Psihologiâ i pravo, 2023)
The article considers the peculiarities of professional demand and motivational profile of the personality of employees of operational subdivisions and patrol-guard service of the police. The sample is represented by 89 employees of internal affairs bodies in age from 29 to 36 years, with the service experience of 2-3 years. Purpose of the study: to determine the influence of the specifics of service activity, motivation and social characteristics on the experience of professional demand for police officers. Methods: anonymous questionnaire of assessment of socio-psychological factors; methodology "Professional demand for personality" (E.V. Kharitonova, B.A. Yasko); questionnaire "Motivational profile" (S. Ritchie, P. Martin). As a result of the study it was found that the specifics of service activities of police officers and their motivation have a significant impact on the overall level of professional demand for personality and its individual components, as well as on the socio-psychological adaptation, "turnover" and psychological health of specialists. Operational unit officers differ from patrol officers (p ≤ 0,05) with a more harmonious profile of the professional demand for personality. В статье рассмотрены особенности профессиональной востребованности и мотивационный профиль личности сотрудников оперативных подразделений и патрульно-постовой службы полиции. Выборка представлена 89 сотрудниками органов внутренних дел в возрасте от 29 до 36 лет, со стажем службы 2-3 года. Цель исследования: определение влияния специфики служебной деятельности, мотивации и социальных характеристик на переживания профессиональной востребованности сотрудников полиции. Методы: анонимная анкета оценки социально-психологических факторов; методика «Профессиональная востребованность личности» (Е.В. Харитонова, Б.А. Ясько); опросник «Мотивационный профиль» (Ш. Ричи, П. Мартина). В результате исследования установлено, что специфика служебной деятельности сотрудников полиции и их мотивация оказывают существенное влияние на общий уровень профессиональной востребованности личности и его отдельные компоненты, а также на социально-психологическую адаптацию, «текучесть кадров» и психологическое здоровье специалистов. Сотрудники оперативных подразделений отличаются от сотрудников патрульно-постовой службы (p ≤ 0,05) более гармоничным профилем профессиональной востребованности личности.